Microsoft SQL server 2008 MDX : step by step - Smith, Bryan C. (Step by step (Redmond, Wash.), 2009)
Teach yourself the Multidimensional Expressions (MDX) query language--one step at a time. With this practical, learn-by-doing tutorial, you'll build the core techniques for using MDX with Analysis Services to deliver high-performance business intelligence solutions. Discover how to: Construct and execute MDX queries Work with tuples, sets, and expressions Build complex sets to retrieve the exact data users need Perform aggregation functions and navigate data hierarchies Assemble time-based business metrics Customize an Analysis Services cube through the MDX script Implement dynamic security to control data access Develop MDX-driven reports in SQL Server Reporting Services CD features: Practice exercises Database and code samples Fully searchable eBook.